Human Security and Its Impact on Political, Economic, and Social Development in Indonesia: A Study of Joko Widodo’s Administration from 2014 to 2024 - Asih Purwanti; Yufita Ng (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
This study analyzes the implementation of human security in Indonesia during the administration of President Joko Widodo (2014–2024). Human security, which places individuals at the center of protection and development, encompasses seven main pillars: economic security, food security, health security, environmental security, personal security, community security, and political security. This study uses a descriptive-qualitative approach with secondary data from government documents, NGO reports, and academic studies. The results show significant progress in improving economic security through poverty alleviation programs such as the Family Hope Program (PKH) and large-scale infrastructure development projects. The National Health Insurance Program (JKN) has expanded health coverage, improving health security for millions of people. In terms of food security, the government's food estate program and agricultural diversification efforts have increased local food production, although challenges in distribution and sustainability remain. Environmental security has improved with a decline in deforestation rates, although illegal deforestation and land conflicts still occur. Despite successes in some areas, challenges to civil rights and political security remain, with restrictions on freedom of speech and the weakening of anti-corruption institutions. In conclusion, the integration of human security into Indonesia's development policies needs to be strengthened, particularly in political and civil rights, to ensure a comprehensive and sustainable future for all citizens.Penelitian ini menganalisis implementasi keamanan insani di Indonesia selama pemerintahan Presiden Joko Widodo (2014–2024). Keamanan insani, yang menempatkan individu sebagai pusat perlindungan dan pengembangan, mencakup tujuh pilar utama: keamanan ekonomi, keamanan pangan, keamanan kesehatan, keamanan lingkungan, keamanan pribadi, keamanan komunitas, dan keamanan politik. Penelitian ini menggunakan pendekatan deskriptif-kualitatif dengan data sekunder dari dokumen pemerintah, laporan LSM, dan studi akademis. Hasil penelitian menunjukkan kemajuan signifikan dalam meningkatkan keamanan ekonomi melalui program pengentasan kemiskinan seperti Program Keluarga Harapan (PKH) dan proyek pembangunan infrastruktur skala besar. Program Jaminan Kesehatan Nasional (JKN) telah memperluas cakupan kesehatan, meningkatkan keamanan kesehatan bagi jutaan orang. Dalam hal ketahanan pangan, program food estate dan upaya diversifikasi pertanian pemerintah telah meningkatkan produksi pangan lokal, meskipun tantangan dalam distribusi dan keberlanjutan masih ada. Keamanan lingkungan membaik dengan penurunan laju deforestasi, meskipun deforestasi ilegal dan konflik lahan masih terjadi. Meskipun berhasil di beberapa bidang, tantangan hak sipil dan keamanan politik tetap ada, dengan pembatasan kebebasan berbicara dan pelemahan lembaga antikorupsi. Sebagai kesimpulan, integrasi keamanan insani dalam kebijakan pembangunan Indonesia perlu diperkuat, khususnya dalam hak-hak politik dan sipil, untuk memastikan masa depan yang komprehensif dan berkelanjutan bagi seluruh warga negara.